ANALYSIS OF DECISION MAKING ON MSMEs IN THE COVID-19 PANDEMIC - Ricardo, Ricardo; Andri Yandi (Dinasti International Journal of Digital Business Management, 2021)
During the current covid-19 pandemic, MSME actors are objects that really feel the impact. Inevitably, MSME actors must rack their brains to make decisions quickly, accurately, and produce clear goals. Management as a science to be a guide for business actors provides knowledge about decision making and its stages. There is not only one type of decision making that can be used by MSME actors. The choice of this type of decision is important, because later it will be used as a guide whether it is appropriate to use a certain type of decision during the COVID-19 pandemic. Decisions taken by MSME actors must also be in accordance with the health protocols touted by the government. This article will explain in detail what MSMEs are, what decision-making is and the stages, what types of decisions can be chosen, the factors that influence decision-making. the relationship between MSMEs and decision making as well as an explanation of the step-by-step analysis of decision-making by MSME actors during this covid-19 pandemic. The advice given in writing this article is that MSME actors need to identify problems critically and make various efforts by making the right decisions. The need to innovate and view that the Covid-19 pandemic situation is not an obstacle but as a means of opportunity to do business that is beneficial to oneself and others.